The Emirati Strategy towards East African Countries Geopolitical Motives and Drivers (قضايا سياسية, 2024)
Abstract The United Arab Emirates occupies very important international and regional position that pushed it be among the most influential actors in many regions.Perhaps the most prominent of which is the Horn of Africa region because of its strategic position , which is more specific , making it a focus of attention , many international powers , this study came as an attempt to answer the main problem, which is, to what extent was the Emirate strategy including the number of effective and influential deposits and engines in the Horn of Africa on the geopolitics of the region. The study also included an understanding of the motives and drivers of the Emirati strategy and its reflection at home and abroad, as well as the pattern of its presence that changed according to the variables of the East region Middle East and The Challenges of the Horn of Africa.